Dendritic Cell-Derived TSLP Negatively Regulates HIF-1α and IL-1β During Dectin-1 Signaling - Elder, Matthew J.; Webster, Steve J.; Fitzmaurice, Timothy J.; Shaunak, Aran S. D.; Steinmetz, Martin; Chee, Ronnie; Mallat, Ziad; Cohen, E. Suzanne; Williams, David L.; Gaston, J. S. Hill; Goodall, Jane C. (Frontiers in Immunology, 2019)
Thymic stromal lymphopoietin (TSLP) is a functionally pleotropic cytokine important in immune regulation, and TSLP dysregulation is associated with numerous diseases. TSLP is produced by many cell types, but has predominantly been characterised as a secreted factor from epithelial cells which activates dendritic cells (DC) that subsequently prime T helper (TH) 2 immunity. However, DC themselves make significant amounts of TSLP in response to microbial products, but the functional role of DC-derived TSLP remains unclear. We show that TSLPR signalling negatively regulates IL-1β production during dectin-1 stimulation of human DC. This regulatory mechanism functions by dampening Syk phosphorylation and is mediated via NADPH oxidase-derived ROS, HIF-1α and pro-IL-1β expression. Considering the profound effect TSLPR signalling has on the metabolic status and the secretome of dectin-1 stimulated DC, these data suggest that autocrine TSLPR signalling could have a fundamental role in modulating immunological effector responses at sites removed from epithelial cell production of TSLP.